A history and evaluation of catch‐only stock assessment models. Issue 3 (16th December 2021) - Ovando, Daniel; Free, Christopher M.; Jensen, Olaf P.; Hilborn, Ray
Abstract: Understanding the status of fish stocks is a critical step in ensuring the ecological and economic sustainability of marine ecosystems. However, at least half of global catch and a vast majority of global fisheries lack formal stock assessments, largely due to a lack of sufficient data. Catch data, loosely referring to any catch records be it inclusive of discards or not, are the only type of fishery data available across a wide range of fisheries at a global scale. This has given rise to a long list of so‐called "catch‐only" models, intended to estimate aspects of stock status based primarily on characteristics of a fishery's catch history. In this paper, we review the history, performance and potential of "catch‐only" models to estimate stock biomass status. While individual catch‐only models often report good performance, repeated efforts to examine the performance of these models have consistently found them to be imprecise and biased when applied to new data‐limited fisheries. We demonstrate that a large reason for this is the simple lack of information on stock status contained in the shape of a catch history alone. Off‐the‐shelf use of catch‐only models can lead to poor and biased estimates of stock status, potentially hindering efforts at effective management.